2015
DOI: 10.5624/isd.2015.45.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Lateral pterygoid muscle volume and migraine in patients with temporomandibular disorders

Abstract: PurposeLateral pterygoid muscle (LPM) plays an important role in jaw movement and has been implicated in Temporomandibular disorders (TMDs). Migraine has been described as a common symptom in patients with TMDs and may be related to muscle hyperactivity. This study aimed to compare LPM volume in individuals with and without migraine, using segmentation of the LPM in magnetic resonance (MR) imaging of the TMJ.Materials and MethodsTwenty patients with migraine and 20 volunteers without migraine underwent a clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 16 publications
(25 reference statements)
2
14
0
Order By: Relevance
“…Of the masticatory muscles, the lateral pterygoid muscle may be the most commonly involved in temporomandibular disorders. In patients with such disorders, abnormal activity of the lateral pterygoid muscle is occasionally observed and hyperactivity of the superior head of the lateral pterygoid muscle may lead to degenerative arthritic changes at the TMJ . The findings of the present study indicate that anterior movement of the bite position during unilateral teeth clenching promotes activity of the superior head of the ipsilateral lateral pterygoid muscle and thereby induces the developments of ipsilateral TMJ disorders.…”
Section: Discussionsupporting
confidence: 50%
“…Of the masticatory muscles, the lateral pterygoid muscle may be the most commonly involved in temporomandibular disorders. In patients with such disorders, abnormal activity of the lateral pterygoid muscle is occasionally observed and hyperactivity of the superior head of the lateral pterygoid muscle may lead to degenerative arthritic changes at the TMJ . The findings of the present study indicate that anterior movement of the bite position during unilateral teeth clenching promotes activity of the superior head of the ipsilateral lateral pterygoid muscle and thereby induces the developments of ipsilateral TMJ disorders.…”
Section: Discussionsupporting
confidence: 50%
“…The present findings underscore the clinical importance of a detailed evaluation and the application of therapies directed at the LPM. Lopes (2015) 32 found that individuals with simultaneous diagnoses of TMD and migraine tend to exhibit hypertrophy of the LPM and have greater pain symptoms during palpation of this muscle. The authors also found strong associations between myofascial pain and both disc displacement and arthralgia in the diagnosis using the RDC/ TMD.…”
Section: Referencesmentioning
confidence: 99%
“…However, the methodology for measuring the maxillary sinus may influence considerably the volume; the internal anatomy of maxillary sinuses is very complex and irregular, with presence of septs and other anatomical variations. Only specific software to calculate the actual segmented volume can be used to this measurement, providing accurate volume measurements by images (7,14,16). Prior to such use of segmented tridimensional images, the methods were more laborious and less precise.…”
Section: Discussionmentioning
confidence: 99%